DIFFERENTIATED TEACHING OF INFORMATICS AT PEDAGOGICAL HIGHER INSTITUTION - Alexander N. Alekseev; Elena N. Korol (Открытое образование (Москва))
This article analyzes the possibility of using criteria of importance for the taught material. It can be employed to differentiate computer science education for students at pedagogical institutions in learning at the humanities departments.